The Role of Work Motivation as a Mediator in the Influence of Communication and Workload on Employee Performance at Warmadewa University - SARI, Ni Wayan Diah Kartika; DHARMANEGARA, I. B. Agung; LAKSMI, Putu Ayu Sita (International Journal of Environmental, Sustainability, and Social Science, 2024)
The objective of this study is to ascertain the function of work motivation as an intermediary in the impact of communication and workload on employee performance at Warmadewa University. The research at Warmadewa University focuses on the relationship between communication and workload as independent variables, work motivation as a mediating component, and employee performance as the dependent variable. This study used Partial Least Square analysis to ascertain the function of work motivation as a mediator in the impact of communication and workload on employee performance at Warmadewa University. The survey included a total of 248 regular staff that were employed at Warmadewa University, Bali. The research employed the proportionate stratified random sampling approach, with a total of 153 samples. This study utilizes primary data, which was gathered by the distribution of questionnaires to the whole research sample. The research findings indicate that there is a positive and statistically significant correlation between communication and employee performance at Warmadewa University. The workload has a detrimental and statistically significant impact on employee performance at Warmadewa University. The relationship between communication and job motivation of employees at Warmadewa University is both favorable and substantial. The workload has a detrimental and substantial impact on the work motivation of employees at Warmadewa University. Work motivation positively and significantly impacts employee performance at Warmadewa University. Work motivation acts as a mediator between communication and employee performance at Warmadewa University. Similarly, work motivation also acts as a mediator between workload and employee performance at Warmadewa University.